1991
DOI: 10.2170/jjphysiol.41.443
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in the Rate of Amylase Release Induced by Various Secretagogues Examined in Isolated Rat Parotid Cells by Using Column Perifusion.

Abstract: Isolated parotid acinar cells were perifused in small columns by embedding them in Bio-Gel P-2 beads as an inert supporting matrix, and the effect of carbamylcholine, substance P, and isoproterenol on the rate of amylase release was examined by measuring amylase activity in the effluent. Amylase release by continuous stimulation with carbamylcholine and substance P was biphasic. They caused a rapid and large increase in the rate of amylase release that reached maximum 30 to 60s after the onset of stimulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Acini Perifusion-Isolated acini were suspended in 1 ml of Bio-Gel P2 beads and perfused at a rate of 1 ml/min at 37°C using a peristaltic pump as previously described (38,39). Samples were collected each min over 20 min for amylase analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acini Perifusion-Isolated acini were suspended in 1 ml of Bio-Gel P2 beads and perfused at a rate of 1 ml/min at 37°C using a peristaltic pump as previously described (38,39). Samples were collected each min over 20 min for amylase analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Using a perifusion system to monitor secretion from a single group of cells over time demonstrates secretion initially peaks at 1 min and decreases over 2-3 min followed by a second prolonged phase that peaks and declines to near the initial constitutive levels over 20 min (Fig. 3A) (38,39). In VAMP8 Ϫ/Ϫ acini the initial rapid phase is slightly delayed by 1 min then quickly decays to constitutive levels by 3-5 min (see the dotted line) followed by a further decrease that approaches the constitutive levels seen in WT acini.…”
Section: (42) Vamp8mentioning
confidence: 99%
“…Although -receptor stimulation dominantly provokes amylase release, stimulation of VIP and muscarinic receptors also evokes amylase release via the increases in intracellular cAMP and Ca 2+ concentrations, respectively, in rat parotid acinar cells (Scott & Baum, 1985;Yoshimura & Nezu, 1991). Then we next examined the effect of ethacrynic acid on amylase release induced by VIP and carbachol, a muscarinic agonist.…”
Section: No Effect Of Ethacrynic Acid On Vip-and Carbachol-induced Ammentioning
confidence: 99%
“…Intracellular calcium also induces small amounts of amylase secretion (Putney, 1986;Yoshimura & Nezu, 1992). Yoshimura et al developed a perfusion system which shows the velocity of amylase release in 30 s increments (Yoshimura & Nezu, 1991;. Results with this system clearly indicated that the time courses of secretion induced by cAMP-producing agonists and calciummobilizing agonists are di!erent and characteristic: secretion by the cAMP-producing agonist isoproterenol (IPR) increases gradually to reach maximum about 5 min after the onset of FIG.…”
Section: Introductionmentioning
confidence: 99%